ANALISIS YURIDIS TERHADAP PERUBAHAN ISI AKTA NOTARIS TANPA PERSETUJUAN PARA PIHAK (STUDI PUTUSAN MAHKAMAH AGUNG NO.1003K/PID/2015) - ADELBERD S SIMAMORA (PREMISE LAW JURNAL, 2017)
Changing the content of a deed by a Notary without notification to one of the parties is one of the actions against the law. In one case, the Notary together with the first party, Bonar Saragih, and a witness, Mangapul Hutahaean, have changed a Notarial deed and did not notify the changes and give a copy of the original deed to the Second Party, Daniel Freddy Sinambela. This has caused one-sided injury to Daniel Freddy Sinambela. This problem has been made the ground to prosecute the Notary for making a counterfeit letter or for counterfeiting a letter according to Article 264 paragraph (1) of the Criminal Code; thus, the Notary has to account for the authentic deed containing criminal element. The legal consequence caused by the Notary who had made changes in a deed which were not in accordance with one of the parties’ wish is to contain the elements of a counterfeit. The Notary involved in the action against the law which is proven that every deed made is not sourced from the regulations stipulated in the prevailing laws and regulation can be punished and addressed. His/her action can be accounted for by Administrative Law, Civil Law and Criminal Law. By the Civil Law the Notary can be addressed for compensation for the cost, indemnity and interest. In Administrative law, the Notary can be addressed for oral warning, written notice, suspension, an honorable discharge, and a disrespectful discharge. The Notary’s responsibility for the deed he/she makes according to criminal law is not regulated in the Law No. 2/2014 on the Amendments to the Law No.30/2004 on Notary, but the Notary can be convicted if he/she commits a crime.